Infant feeding practices and breastfeeding experiences of mothers of filipino infants aged 6-23 months old breastfed beyond 6 months in a low income urban community - Babilonia, Maria Charito D.
Introduction: Adequate nutrition is significant to child health and development. The aspects of infant feeding beyond 6 months include both continued breastfeeding and complementary feeding. The period of greatest risk for the development of malnutrition corresponds to the period of complementary feeding and continued breastfeeding; both are important components of optimal infant nutrition. Improving infant feeding practices is a direct and effective strategy for preventing malnutrition. Methodology: This is a descriptive study consisting of a two-part face-to-face interview of mothers who are still breastfeeding 6-23 month of old infants. The first part of the interview was a structured interview using WHO food intake tool based on current status. The second part of the interview used open-ended questionnaire on mother?s breastfeeding experiences. The study was carried out in Urban Barangay, Paliparan III, Dasmarinas, Cavite. Results: Continued breastfeeding rates in the study population were as follows: 53%, 48%, and 41% among 6-11 months old, 12-7 months old, and 18-23 months old infants, respectively. A total of sixty(60) mothers ? infant pairs were included in the study. Complementary feeding was started before 6 months in 46% of the infants, while 4% were introduced to complementary feeding later that 6 months. All infants started breastfeeding at birth. The mothers described their positive and difficult experiences in breastfeeding beyond 6 months. Positive experiences were attributed to breastfeeding?s health benefits on the infants; breastfeeding for them is comfortable and natural; it is the time of bonding moment; it has provided the mothers the feeling of being able to put the infant in safe and secure position when breastfeeding; and it has made feeding the infant with other foods easier. The difficulties reported were mostly related to infant?s teething; other difficulties were maternal factors such as the experience of hunger, feeling of weakness, and perception of weight loss. Breastfeeding also prevented the mothers from performing other duties such as household chores and looking after other children. Concerns on fertility issues, which were central to both women and their partners, were likewise highlighted. Conclusions: Infant feeding practices of the study population is less than ideal. The practices were not in accordance with the feeding guidelines for breastfeed children. Mothers were aware of the effects of breastfeeding on infants but had little sights on how breastfeeding beyond 6 months benefit them as well. Recommendation: Both complementary feeding and continued breastfeeding must be promoted together to maximize benefits for both mothers and infants. Breastfeeding promotion beyond the first 6 months must emphasize maternal health benefits